Towards an economic approach for studying of divorces in Macedonia - Goran Miladinov (Journal of Contemporary Economic and Business Issues, 2015)
This paper examines the impact of trends in female labor force participation on crude divorce rate in Macedonia for the period from 1996 to 2013 in the context of a broader examination of the relationship between the economic factors and their effects and the risk of divorce. In light of the changing demographics of divorce patterns, we investigate the relationship between economic variables and divorce, controlling for a set of social and life course variables.The analyses was conducted using an econometric simultaneous equation model (SEM) and 2SLS method. The results indicated that there is simultaneous relationship between the mean age at first marriage for women, female labor force participation and the crude divorce rate. We find that factors that improve financial stability are positively associated with divorce trends. Understanding the effects of female labor force participation is therefore important to explain divorce trends.Our results suggest that the influence of the the unemployment elasticity and Consumer price index elasticity on divorce have declined and almost and disappeared. We also find that a range of other social and life course factors are also important to be considered relevant whether or not a person divorces.
Keywords: C36; C26; C52; J12; J21; E24; 330; marriage dissolution; SEM; 2SLS method; mean age at first marriage; female labor force